A rare cause of metabolic acidosis: ketoacidosis in a non-diabetic lactating woman. (4th September 2017) - Sloan, Gordon; Ali, Amjad; Webster, Jonathan
Summary: Ketoacidosis occurring during lactation has been described infrequently. The condition is incompletely understood, but it appears to be associated with a combination of increased metabolic demands during lactation, reduction in carbohydrate intake and acute illness. We present a case of a 27-year-old woman, 8 weeks post-partum, who was exclusively breastfeeding her child whilst following a low carbohydrate diet. She developed gastroenteritis and was unable to tolerate an oral diet for several days. She presented with severe metabolic acidosis on admission with a blood 3-hydroxybutyrate of 5.4 mmol/L. She was treated with intravenous dextrose and intravenous sodium bicarbonate, and given dietary advice to increase her carbohydrate intake. She made a rapid and full recovery. We provide a summary of the common causes of ketoacidosis and compare our case with other presentations of lactation ketoacidosis. Learning points: Ketoacidosis in the lactating woman is a rare cause of raised anion gap metabolic acidosis. Low carbohydrate intake, starvation, intercurrent illness or a combination of these factors could put breastfeeding women at risk of ketoacidosis. Ketoacidosis in the lactating woman has been shown to resolve rapidly with sufficient carbohydrate intake and intravenous dextrose. Early diagnosis and prompt treatment are essential because the condition is reported to be reversible with a low chance of recurrence with appropriate dietary advice.